2019
DOI: 10.13189/lls.2019.070505
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse in Academic Writing: An Investigation of Saudi EFL Students' Research Articles

Abstract: This study investigated the type and frequency of metadiscourse markers used in fifty research articles written by Saudi EFL college students. In analyzing the data, Hyland's (2005) model of metadiscourse was adopted. The findings showed that there are significant differences in the frequency of interactive and interactional metadiscourse. The students employed more interactive metadiscourse markers than interactional ones. The analysis further revealed that transitions occurred most often in the research arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The most prominent and the least metadiscourse features produced by BA course The two figures above show the metadiscourse features produced by computer science (CS) and business administration (BA) courses. Based on the interactive metadiscourse graph, Transition markers were the highest feature used by CS students with 945 which is similar to the result by Alkhathlan (2019). Transition Markers link the relations between main clauses like in addition, but, thus, and, first, next etc.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The most prominent and the least metadiscourse features produced by BA course The two figures above show the metadiscourse features produced by computer science (CS) and business administration (BA) courses. Based on the interactive metadiscourse graph, Transition markers were the highest feature used by CS students with 945 which is similar to the result by Alkhathlan (2019). Transition Markers link the relations between main clauses like in addition, but, thus, and, first, next etc.…”
Section: Resultssupporting
confidence: 52%
“…Hence, we conclude that CS students preferred to use the features in interactive metadiscourse as compared to interactional metadiscourse and likewise to BA group. Apart from that, according to interactive metadiscourse graph, the least metadiscourse feature was Evidential with 66 produced by BA students while in interactional metadiscourse graph, the least metadiscourse feature was Attitude markers with 16 produced by CS students in which agreed with the result of study by Alkhathlan (2019). Attitude Markers are to indicate the writer's opinion or assessment of a proposition such as 'I agree, I am amazed, appropriate, correctly, dramatic, hopefully, unfortunately etc.…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, transitions and hedges were found to be the most frequent markers in both genres. Alkhathlan (2019) investigated the type and frequency of occurrence of MDMs in 50 RAs by Saudi EFL college students. It was found that the students employed more interactive metadiscourse s than interactional ones.…”
Section: Previous Studiesmentioning
confidence: 99%
“…This size accompanying one, two or three sections was scrutinized and the results might be questionable. Third, Alharbi (2021) and Alkhathlan (2019) investigated Arab scholars' use of MDMs in the Arab context. Nevertheless, the two studies suffer from the shortages mentioned above and Alkhathlan (2019) collected his data from college students who might not be proficient writers.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation